Clinical characteristics, time course, treatment and outcomes of patients with immune checkpoint inhibitor-associated myocarditis. Issue 6 (23rd June 2021) - Puzanov, Igor; Subramanian, Poornima; Yatsynovich, Yan V; Jacobs, David M; Chilbert, Maya R; Sharma, Umesh C; Ito, Fumito; Feuerstein, Steven G; Stefanovic, Filip; Switzer, Benjamin; Hicar, Mark D; Curtis, Anne B; et al.
Abstract : Background: Immune checkpoint inhibitors (ICI) have emerged as a front-line therapy for a variety of solid tumors. With the widespread use of these agents, immune-associated toxicities are increasingly being recognized, including fatal myocarditis. There are limited data on the outcomes and prognostic utility of biomarkers associated with ICI-associated myocarditis. Our objective was to examine the associations between clinical biomarkers of cardiomyocyte damage and mortality in patients with cancer treated with ICIs. Methods: We retrospectively studied 23 patients who developed symptomatic and asymptomatic troponin elevations while receiving ICI therapy at a National Cancer Institute-designated comprehensive cancer center. We obtained serial ECGs, troponin I, and creatine kinase-MD (CK-MB), in addition to other conventional clinical biomarkers, and compared covariates between survivors and non-survivors. Results: Among patients with myocarditis, higher troponin I (p=0.037) and CK-MB (p=0.034) levels on presentation correlated with progression to severe myocarditis. Higher troponin I (p=0.016), CK (p=0.013), and CK-MB (p=0.034) levels were associated with increased mortality, while the presence of advanced atrioventricular block on presentation (p=0.088) trended toward increased mortality. Weekly troponin monitoring lead to earlier hospitalization for potential myocarditis (p=0.022) and was associated with decreased time to steroid initiation (p=0.053) and improved outcomes. Conclusions: Routine troponin surveillance may be helpful in predicting mortality in ICI-treated patients with cancer in the early phase of ICI therapy initiation. Early detection of troponin elevation is associated with earlier intervention and improved outcomes in ICI-associated myocarditis. The recommended assessment and diagnostic studies guiding treatment decisions are presented.